Negative electrode for fluoride ion secondary battery and fluoride ion secondary battery having the same
By adding Li3AlF6 to modified AlF3 formed by doping lithium metal in aluminum fluoride and optimizing its particle size and crystalline state, the problems of electrical insulation and low ion conductivity in the prior art are solved, and a higher Battery capacity and higher active substance utilization and Coulomb efficiency.
Patent Information
- Application Number
- CN202210094145.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-26
- Filing Date
- 2022-01-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-26
AI Technical Summary
In the fluoride ion secondary battery, the modified AlF3 formed by doping lithium metal in aluminum fluoride is difficult to increase the concentration and battery capacity of the negative electrode active material due to electrical insulation and low ion conductivity.
Li3AlF6 is added as the negative electrode active material to modified AlF3 doped with lithium metal in aluminum fluoride, and the particle size and crystalline state of Li3AlF6 are optimized through the synthesis method to improve its density and ionic conductivity in the battery.
By increasing the concentration and ionic conductivity of Li3AlF6, the battery capacity of fluoride ion secondary batteries is significantly increased, and the utilization rate of active substances and Coulomb efficiency are improved.
Smart Images

Figure CN114792774B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a fluoride ion secondary battery and a fluoride ion secondary battery having the negative electrode. Background Art
[0002] Currently, fluoride ion secondary batteries using fluoride ions as carriers have been proposed (for example, see Patent Documents 1 to 6). In recent years, fluoride ion secondary batteries are expected to have battery characteristics superior to those of lithium ion secondary batteries, and various studies have been conducted.
[0003] For example, aluminum-based materials are listed as candidates for negative electrode active materials for fluoride ion secondary batteries. Among them, the use of aluminum fluoride has been studied, but there is a problem that aluminum fluoride has electrical insulation properties and therefore has difficulty in causing electrochemical reactions.
[0004] [Prior Technical Literature]
[0005] (Patent Document)
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-87403
[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-50113
[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-29206
[0009] Patent Document 4: Japanese Patent Application Publication No. 2018-206755
[0010] Patent Document 5: Japanese Patent Application Publication No. 2018-198130
[0011] Patent Document 6: Japanese Patent Application Publication No. 2018-92863 Summary of the invention
[0012] [Problems to be solved by the invention]
[0013] Therefore, the applicant has realized a fluoride ion secondary battery using modified AlF3 formed by doping aluminum fluoride with lithium metal as the negative electrode active material, but the current situation is that the battery characteristics need to be further improved. In particular, since the modified AlF3 doped with lithium metal in aluminum fluoride does not have good ion conductivity, it is impossible to increase the concentration of the negative electrode active material in the negative electrode, and it is difficult to increase the battery capacity.
[0014] The present invention has been made in view of the above, and an object of the present invention is to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries.
[0015] [Technical means to solve the problem]
[0016] (1) The present invention provides a negative electrode for a fluoride ion secondary battery, which includes a negative electrode active material, wherein the negative electrode active material includes Li3AlF6.
[0017] (2) Alternatively, in the negative electrode for a fluoride ion secondary battery of (1), a content of the negative electrode active material in the negative electrode for a fluoride ion secondary battery is 25 mass % or less.
[0018] (3) Optionally, in the negative electrode for a fluoride ion secondary battery of (1) or (2), the aforementioned Li3AlF6 is amorphous.
[0019] (4) Optionally, in the negative electrode for a fluoride ion secondary battery of any one of (1) to (3), the average particle size of the aforementioned Li3AlF6 is on the order of microns.
[0020] (5) The present invention also provides a fluoride ion secondary battery comprising the negative electrode for a fluoride ion secondary battery according to any one of (1) to (4).
[0021] (Effects of the Invention)
[0022] According to the present invention, it is possible to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a diagram illustrating a method for synthesizing Li3AlF6 as a negative electrode active material according to one embodiment of the present invention.
[0024] Figure 2 This is an X-ray diffraction spectrum diagram of Li3AlF6 as the negative electrode active material in the above embodiment.
[0025] Figure 3 It is a graph showing the characteristics of Li3AlF6 and existing modified AlF3.
[0026] Figure 4 This is a diagram showing an example of a method for producing a negative electrode for a fluoride ion secondary battery according to one embodiment of the present invention.
[0027] Figure 5 This is a diagram showing an example of a conventional method for producing a negative electrode for a fluoride ion secondary battery.
[0028] Figure 6 It is a Nuclear Magnetic Resonance (NMR) spectrum chart of Li3AlF6 as the negative electrode active material in the above embodiment.
[0029] Figure 7 The graph shows the charge and discharge curves of the negative electrode half-cells for fluoride ion secondary batteries of Example 1 and Comparative Example 1.
[0030] Figure 8 The graph shows the charge and discharge curves of the negative electrode half-cells for fluoride ion secondary batteries of Example 2 and Comparative Example 2. DETAILED DESCRIPTION
[0031] Hereinafter, one embodiment of the present invention will be described in detail with reference to the drawings.
[0032] [Negative electrode for fluoride ion secondary battery]
[0033] The negative electrode for fluoride ion secondary battery of this embodiment contains Li3AlF6 as the negative electrode active material. So far, no negative electrode for fluoride ion secondary battery containing Li3AlF6 has been found. The negative electrode for fluoride ion secondary battery of this embodiment is characterized by containing Li3AlF6.
[0034] Li3AlF6 acts as a negative electrode active material during charge and discharge. Specifically, Li3AlF6 releases fluoride ions F during charge. - , absorbing fluoride ions F during discharge - Li3AlF6 can be synthesized, for example, in the following manner.
[0035] Figure 1 FIG. 1 is a diagram showing a method for synthesizing Li3AlF6 as a negative electrode active material according to the present embodiment. Figure 1 As shown, first, LiF and AlF3 are mixed in a ratio of LiF:AlF3=3mol:1mol. Figure 1 In the example shown, 2.4 g of LiF and 2.6 g of AlF3 are mixed. Next, the mixture is subjected to a ball mill pulverization treatment, for example, at 400 rpm, for 15 minutes, for 40 cycles, and then subjected to a sintering treatment, for example, at 900°C for 3 hours. After sintering, the mixture is pulverized to obtain Li3AlF6 as the negative electrode active material of this embodiment.
[0036] Here, the temperature of the sintering treatment is preferably in the range of 850°C to 900°C. This is because the melting point of the raw material LiF is 850°C, so if the sintering temperature is within this range, the molten LiF and AlF3 will be uniformly mixed. If the sintering temperature exceeds 900°C, the weight after sintering begins to decrease significantly and the raw material evaporates, which is not preferred.
[0037] In addition, when the sintering temperature is 850°C to 900°C, the sintering time is preferably in the range of 2 hours to 3 hours. If the sintering time is less than 2 hours, the reaction between LiF and AlF3 is insufficient, which is not preferred. If the sintering time exceeds 3 hours, the raw material evaporates and the yield decreases, which is not preferred.
[0038] The pulverization after the sintering process can be performed in, for example, an agate mortar, and the pulverized particles are fine particles. The fine particles are further pulverized by a ball mill pulverization process when preparing the negative electrode mixture powder described later.
[0039] Figure 2 This is an X-ray diffraction spectrum of Li3AlF6, which is the negative electrode active material of this embodiment. Figure 2 From top to bottom, the following are shown in order: Figure 1 The X-ray diffraction spectra of the synthesized product, AlF3 (theoretical calculated value), LiF (theoretical calculated value), and Li3AlF6 (theoretical calculated value) obtained by the synthesis method. Figure 2 As shown, according to Figure 1 In the X-ray diffraction spectrum of the synthetic product synthesized by the synthesis method, the peaks derived from AlF3 and LiF as raw materials disappeared, while the peaks derived from Li3AlF6 were observed. Figure 2 The X-ray diffraction spectrum can confirm that Figure 1 The synthesis method can synthesize Li3AlF6.
[0040] The negative electrode active material of this embodiment is preferably amorphous. Figure 2 It can be seen from the X-ray diffraction spectrum that the Li3AlF6 synthesized as the negative electrode active material in the above manner is crystalline, but amorphization occurs in the manufacturing process of the negative electrode for the fluoride ion secondary battery of the present embodiment described later. It is believed that the Li3AlF6 synthesized as the negative electrode active material in the above manner has an unstable crystal structure, and it is believed that the crystal structure will be destroyed by the ball mill crushing process in the manufacturing process described later, and amorphization will be performed. In this way, since the negative electrode active material of the present embodiment is amorphous, Li3AlF6 can be closely combined with the solid electrolyte and the conductive auxiliary agent to form a high-quality interface.
[0041] The content of Li3AlF6 in the negative electrode for fluoride ion secondary battery of the present embodiment is preferably below 25 mass %. Here, as described above, in the modified AlF3 formed by doping lithium metal in aluminum fluoride currently discovered by the present applicant, the upper limit of the content in the negative electrode for fluoride ion secondary battery is 12.5 mass %. In this regard, in the Li3AlF6 of the present embodiment, the upper limit of the content in the negative electrode for fluoride ion secondary battery can be increased to 25 mass %. Thus, according to the present embodiment, the battery capacity can be increased more significantly than before.
[0042] The average particle size of Li3AlF6 as the negative electrode active material in this embodiment is preferably in the micron order. The existing modified AlF3 formed by doping lithium metal in aluminum fluoride is composed of nanoparticles with an average particle size of nanometers. In this regard, in this embodiment, Li3AlF6 as the negative electrode active material is composed of microparticles with an average particle size of micrometers, thereby further improving the density. Therefore, higher ion conductivity can be obtained and the battery capacity can be increased. In addition, in order to obtain Li3AlF6 composed of microparticles with an average particle size of micrometers, it is sufficient to use AlF3 and LiF composed of microparticles with average particle sizes of micrometers as raw materials. In addition, unlike the existing modified AlF3, the Li3AlF6 in this embodiment undergoes a sintering process, so the sintering process also increases the particle size.
[0043] Here, Figure 3 The figure shows the characteristics of Li3AlF6 and the modified AlF3 formed by doping lithium metal in aluminum fluoride. Figure 3 Measured values of the density of Li3AlF6 of the present embodiment and modified AlF3 proposed in the past are shown, and the ion conductivity of the two at 140°C when a fluoride ion secondary battery is assumed to be operating is shown.
[0044] like Figure 3 As shown, Li3AlF6 has a higher density than the existing modified AlF3 and also has a higher ion conductivity. Therefore, the concentration of Li3AlF6 can be increased compared to the modified AlF3, and thus, as described above, the battery capacity can be further increased. In addition, in Li3AlF6, even if the concentration is increased, the volume increase can be suppressed, so the content of the solid electrolyte including the fluoride ion conductive fluoride and the content of the conductive auxiliary agent can be increased, resulting in a higher ion conductivity.
[0045] The negative electrode for the fluoride ion secondary battery of the present embodiment preferably contains a solid electrolyte including a fluoride ion conductive fluoride and a conductive auxiliary agent in addition to the above-mentioned Li 3 AlF 6 as the negative electrode active material.
[0046] The fluoride ion conductive fluoride is not particularly limited as long as it has fluoride ion conductivity. For example, CeBaF x and BaLaF y Fluoride ion conductive fluoride, specifically, Ce 0.95 Ba 0.05 F 2.95 Or Ba 0.6 La 0.4 F 2.4 The fluoride ion conductivity is improved by including these fluoride ion conductive fluorides in the negative electrode for the fluoride ion secondary battery of the present embodiment.
[0047] The average particle size of the fluoride ion conductive fluoride is preferably in the range of 0.1 μm to 100 μm. If the average particle size of the fluoride ion conductive fluoride is within this range, it has high ion conductivity and can form a thin-layer electrode. The more preferred range of the average particle size of the fluoride ion conductive fluoride is 0.1 μm to 10 μm.
[0048] The conductive aid is not particularly limited as long as it has electronic conductivity. For example, carbon black or the like is used as the conductive aid. As carbon black, furnace black, Ketjen black, acetylene black, etc. can be used. By including these conductive aids in the negative electrode for the fluoride ion secondary battery of the present embodiment, electronic conductivity can be improved.
[0049] The average particle size of the conductive additive is preferably in the range of 20 nm to 50 nm. If the average particle size of the conductive additive is in this range, an electrode having a light weight and high electron conductivity can be formed.
[0050] Furthermore, the negative electrode for a fluoride ion secondary battery of the present embodiment may further contain other components such as a binder within a range not impairing the effects of the present embodiment.
[0051] Next, the method for producing the negative electrode for the fluoride ion secondary battery of this embodiment is described with reference to Figure 4 and Figure 5 Explain in detail.
[0052] Here, Figure 4 : is a diagram showing an example of a method for manufacturing a negative electrode for a fluoride ion secondary battery according to this embodiment. Figure 5 1 is a diagram showing an example of a method for manufacturing a negative electrode for a conventional fluoride ion secondary battery. Figure 5 The manufacturing method shown shows a manufacturing method of a negative electrode using modified AlF3 formed by doping lithium metal in existing aluminum fluoride proposed by the applicant.
[0053] exist Figure 4 In an example of the production method of the present embodiment shown in the figure, first, 700 mg of CeBaF as a solid electrolyte containing fluoride ion conductive fluoride is mixed. x (Ce 0.95 Ba 0.05 F 2.95 ) and 50 mg of carbon black (acetylene black AB) as a conductive aid.
[0054] Next, 250 mg of Figure 1 After the Li3AlF6 synthesized by the synthesis method shown in the figure is subjected to ball mill pulverization treatment, for example, 300 rpm, 15 minutes, and 40 cycles. Thus, the mixture LiAlFCB of the negative electrode for the fluoride ion secondary battery of the present embodiment can be obtained. Then, the obtained mixture LiAlFCB is pressed and integrated with a negative electrode collector such as gold foil at a specified pressure to manufacture the negative electrode for the fluoride ion secondary battery of the present embodiment.
[0055] In addition, the mixing ratio of Li3AlF6 and fluoride ion conductive fluoride can be arbitrarily selected. Among them, as mentioned above, the content of Li3AlF6 in the negative electrode for fluoride ion secondary battery is preferably below 25 mass %, and from the viewpoint of increasing the charging capacity, the proportion of fluoride ion conductive fluoride as fluorine source is preferably higher.
[0056] In addition, if you compare Figure 4 The method for producing the negative electrode for the fluoride ion secondary battery of the present embodiment shown in FIG. Figure 5 It can be seen from the existing method for manufacturing a negative electrode for a fluoride ion secondary battery that the difference between the two manufacturing methods is that the negative electrode active material added to the mixture of fluoride ion conductive fluoride and conductive auxiliary agent is different. In the manufacturing method of the negative electrode for a fluoride ion secondary battery of the present embodiment, Li3AlF6 synthesized by the above-mentioned synthesis method is added as the negative electrode active material, so that a negative electrode mixture for a fluoride ion secondary battery consisting of a mixture of fluoride ion conductive fluoride, conductive auxiliary agent and Li3AlF6 can be obtained. In addition, the details of the synthesis method of the modified AlF3 formed by doping lithium metal in aluminum fluoride added to the existing method for manufacturing a negative electrode for a fluoride ion secondary battery are as described in PCT / JP2019 / 039886.
[0057] By the way, when using Figure 4In the negative electrode for the fluoride ion secondary battery of the present embodiment manufactured by the manufacturing method shown, as described above, since Li3AlF6 as the negative electrode active material is unstable, the crystal structure is destroyed by the ball mill treatment, thereby being amorphized. That is, even if the Li3AlF6 as the negative electrode active material of the present embodiment is measured by X-ray diffraction, the peak value cannot be confirmed. Therefore, as a measurement method instead of X-ray diffraction measurement, NMR measurement can be cited. According to the NMR measurement, the amorphized Li3AlF6 as the negative electrode active material of the present embodiment can be detected.
[0058] Figure 6 : is the NMR spectrum of Li3AlF6 as the negative electrode active material of this embodiment. More specifically, Figure 6 According to the above Figure 1 Solid NMR spectrum of Li3AlF6 synthesized by the synthesis method shown. In addition, the measurement conditions of NMR measurement are as follows.
[0059] (NMR measurement conditions)
[0060] NMR device: JEOL "JNM-ECA600"
[0061] Probe: Agilent 1.6mm triple resonance MAS probe
[0062] Temperature: Room temperature
[0063] Rotation condition: 35kHz
[0064] Reference materials: 7 Li is LiCl, 19 F is CFCl3, 27 Al is Al(NO3)3
[0065] like Figure 6 As shown, in the NMR spectrum of the Li3AlF6 synthetic product, a large peak is observed at a chemical shift of 180 ppm. This large peak is attributed to 19 The peak derived from F is a characteristic of Li3AlF6. Therefore, it can be seen that the presence of amorphized Li3AlF6 using the above-mentioned manufacturing method can be confirmed by solid NMR measurement. In addition, a peak of LiF can be observed in the NMR spectrum of the Li3AlF6 synthetic product, but it is the unreacted LiF remaining.
[0066] According to the negative electrode for a fluoride ion secondary battery of the present embodiment described above, the following effects are achieved.
[0067] In the negative electrode for the fluoride ion secondary battery of the present embodiment, it is configured to include Li3AlF6 as a negative electrode active material. As described above, Li3AlF6 has a higher density than the existing modified AlF3 formed by doping lithium metal in aluminum fluoride, and in addition, its own ionic conductivity is also high. Therefore, compared with the existing modified AlF3, the concentration of Li3AlF6 can be increased, and therefore, the battery capacity can be further increased. In addition, in Li3AlF6, even if its concentration is increased, the volume increase can be suppressed, and therefore, the content of the solid electrolyte including the fluoride ion conductive fluoride and the content of the conductive auxiliary agent can be increased, resulting in a higher ionic conductivity and a further increase in the battery capacity.
[0068] In addition, according to the negative electrode for fluoride ion secondary battery of this embodiment, a higher active material utilization rate can be obtained in the first charge and discharge cycle, and a higher coulomb efficiency can also be obtained. Specifically, in the existing modified AlF3, the active material utilization rate is as low as about 40%, and the coulomb efficiency is also as low as 50%. In contrast, according to this embodiment, a higher active material utilization rate of about 70% can be obtained, and a higher coulomb efficiency of about 80% can be obtained.
[0069] [Fluoride ion secondary battery]
[0070] The fluoride ion secondary battery of the present embodiment includes the above-mentioned negative electrode for fluoride ion secondary batteries. In addition, the fluoride ion secondary battery of the present embodiment includes a solid electrolyte layer composed of a solid electrolyte having fluoride ion conductivity and a positive electrode.
[0071] As the solid electrolyte constituting the solid electrolyte layer, a conventionally known solid electrolyte is used. Specifically, the same solid electrolyte as the above-mentioned fluoride ion conductive fluoride can be used.
[0072] As the positive electrode, a currently known positive electrode active material is used, and a positive electrode having a sufficiently high standard electrode potential is preferably used relative to the standard electrode potential of the fluoride ion secondary battery negative electrode of the present embodiment. In addition, a material without fluoride ions is selected as the positive electrode, whereby a battery with charging turned on can be realized. That is, a battery can be manufactured in a discharge state with a lower energy state, and the stability of the active material in the electrode can be further improved.
[0073] Specific positive electrode materials include conductive additives such as Pb, Cu, Sn, Bi, and Ag, binders, etc. For example, a positive electrode mixture containing lead fluoride or tin fluoride, carbon black, etc., a positive electrode material, and a lead foil as a current collector are pressed and integrated at a predetermined pressure to manufacture a positive electrode.
[0074] Therefore, the fluoride ion secondary battery of this embodiment can be manufactured by stacking the negative electrode for fluoride ion secondary battery of this embodiment, the solid electrolyte layer, and the positive electrode in this order. According to the fluoride ion secondary battery of this embodiment, the same effect as the negative electrode for fluoride ion secondary battery of this embodiment can be achieved.
[0075] The present invention is not limited to the above-described embodiments, and modifications and improvements made within the scope that can achieve the object of the present invention are included in the present invention.
[0076] For example, in the above-mentioned embodiment, an example in which the present invention is applied to a solid-state battery is described, but the present invention is not limited thereto. An electrolyte solution may be used in place of a solid electrolyte layer in a fluoride ion secondary battery.
[0077] [Example]
[0078] Next, examples of the present invention will be described, but the present invention is not limited to these examples.
[0079] [Examples 1 and 2]
[0080] according to Figure 4 The manufacturing method of the negative electrode for fluoride ion secondary battery of the present embodiment shown is used to prepare the negative electrode for fluoride ion secondary battery of Examples 1 and 2. Examples 1 and 2 both use Li3AlF6 with an average particle size of micrometer level (10 μm to 100 μm), a fluoride ion conductive fluoride with an average particle size of 0.1 to 100 μm, and a conductive auxiliary agent with an average particle size of 20 to 50 nm. In addition, the content of Li3AlF6 in the negative electrode for fluoride ion secondary battery is set to 12.5% by mass in Example 1 and 25% by mass in Example 2.
[0081] [Comparative Examples 1 and 2]
[0082] according to Figure 5 The conventional method for manufacturing a negative electrode for a fluoride ion secondary battery shown in the figure and the synthesis method described in PCT / JP2019 / 039886 were used to prepare negative electrodes for fluoride ion secondary batteries of Comparative Examples 1 and 2. Both Comparative Examples 1 and 2 used modified AlF3 with an average particle size of nanometers, and the content of modified AlF3 in the negative electrode for a fluoride ion secondary battery was set to 12.5% by mass in Comparative Example 1 and 2 to 25% by mass in Comparative Example 2.
[0083] [Charge and discharge test]
[0084] A half-cell was prepared respectively, and the half-cell used the negative electrode for the fluoride ion secondary battery prepared in each embodiment, and a constant current charge and discharge test was performed. Specifically, a potentiostat (manufactured by Soltron, SI1287 / 1255B) was used, and in a vacuum environment of 140°C, a half-cell with an active material concentration of 12.5% by mass was charged with a current of 0.02mA and discharged with a current of 0.01mA, and a lower limit voltage of -2.35V and an upper limit voltage of -0.1V were set, and a constant current charge and discharge test was applied from the charging current. In addition, for a half-cell with an active material concentration of 25% by mass, a constant current charge and discharge test was applied from the charging current with a current of 0.04mA and a discharge current of 0.02mA, a lower limit voltage of -2.44V and an upper limit voltage of -0.1V were set.
[0085] In addition, as each half-cell, a tablet press was used to press at a pressure of 40 MPa to produce a cylindrical particle-type battery formed by powder pressing. Specifically, gold foil (99.99%, thickness 10 μm) manufactured by Nilaco Co., Ltd. as a negative electrode collector, 10 mg of negative electrode mixture powder for fluoride ion secondary batteries prepared in each embodiment, 200 mg of solid electrolyte, 30 mg of positive electrode mixture powder, positive electrode material, and lead foil (99.99%, thickness 200 μm) manufactured by Nilaco Co., Ltd. as a positive electrode collector were sequentially put into the tablet press to produce each half-cell.
[0086] [Results and Investigation]
[0087] Figure 7 is a graph showing the charge and discharge curves of the negative electrode half-cell for the fluoride ion secondary battery of Example 1 and Comparative Example 1. More specifically, Figure 7 The charge and discharge curves in the first charge and discharge cycle of Example 1 and Comparative Example 1 are shown. Figure 7 As shown, if the content of Li3AlF6 in the negative electrode for fluoride ion secondary battery is 12.5 mass % in Example 1 and the content of modified AlF3 in the negative electrode for fluoride ion secondary battery is 12.5 mass % in Comparative Example 1, the same charging capacity can be obtained. On the other hand, it can be seen that the discharge capacity in Comparative Example 1 is smaller than that in Example 1, and it can be confirmed that the ratio of the discharge capacity to the charging capacity of this embodiment, that is, the coulomb efficiency, is high. Based on this result, it can be confirmed that according to this embodiment, the reversibility of charge and discharge can be improved compared with the past.
[0088] Figure 8 is a graph showing the charge and discharge curves of the negative electrode half-cell for the fluoride ion secondary battery of Example 2 and Comparative Example 2. More specifically, Figure 8 The charge and discharge curves in the first charge and discharge cycle in Example 2 and Comparative Example 2 are shown. Figure 8 As shown, in Comparative Example 2 in which the content of modified AlF3 in the negative electrode for fluoride ion secondary battery is 25 mass%, almost no charge and discharge capacity is obtained. In contrast, in Example 2 in which the content of Li3AlF6 in the negative electrode for fluoride ion secondary battery is 25 mass%, it can be confirmed that a larger charge and discharge capacity is obtained. Based on this result, it can be confirmed that according to this embodiment, the content of Li3AlF6 in the negative electrode for fluoride ion secondary battery can be increased to 25 mass%, and a larger battery capacity than before can be obtained.
[0089] In addition, the actual capacity obtained is expressed as the utilization rate of active materials relative to the theoretical capacity. In this regard, the theoretical capacity of Li3AlF6 is 2.48 mAh, but Figure 8 The results show that the capacity in Example 2 is about 1.7 mAh. According to this example, the active material utilization rate can be as high as about 68%. Figure 8 The results also confirmed that according to Example 2, a discharge capacity of about 1.3 mAh can be obtained relative to a charge capacity of about 1.7 mAh, and a coulombic efficiency as high as about 80% can be obtained.
Claims
1. A negative electrode for a fluoride ion secondary battery, comprising a negative electrode active material, a solid electrolyte including a fluoride ion conductive fluoride, and a conductive auxiliary agent, The negative electrode active material comprises amorphous Li3AlF6, wherein: The content of the amorphous Li3AlF6 in the negative electrode for the fluoride ion secondary battery is greater than 0 mass % and less than or equal to 25 mass %.
2. The negative electrode for a fluoride ion secondary battery according to claim 1, wherein The average particle size of the aforementioned amorphous Li3AlF6 is on the micron level. 3 . A fluoride ion secondary battery comprising the negative electrode for a fluoride ion secondary battery according to claim 1 .
Citation Information
Patent Citations
Fluoride ion battery
JP2017050113A
Fluoride ion all solid state battery
JP2018092863A
Fluoride ion battery
JP2018198130A
Positive electrode active material and fluoride ion battery
JP2018206755A
Fluoride ion battery
JP2019029206A